A MAN IN ROMANCE: THE PORTRAYAL OF THE MALE PROTAGONIST IN NETFLIX’S SERIES “BRIDGERTON” SEASON 1 (2020) - Ha, Thuy Tien; Vu, Thi Phuong Quynh (VNU Journal of Foreign Studies, 2024)
Gender research in the media focuses more on the representation of women and neglects that of men (Brooks & Hébert, 2006; Kimmel et al., 2004). Little research has been conducted to examine the representation of men’s psychological aspects, such as feelings, affection and personality. This paper analyzes Netflix's series Bridgerton Season 1 using a critical discourse analysis approach, to explore how the male protagonist is portrayed visually and linguistically in romance. The findings reveal that while the male protagonist is portrayed as having vulnerabilities and insecurities in love and marriage, he is ultimately depicted with stereotypical masculine traits associated with patriarchal power. Although this depiction of the male protagonist may encourage the audience to embrace the multiplicity of masculinity, it could reinforce male gender norms and raise harmful social expectations on men.